The Position of Customary Court Decisions in Proving Civil Proceedings in State Courts - Happy Trizna Wijaya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research was conducted with a doctrinal or normative method and used a conceptual approach. The normative research method not only examines positive law but also customary law as material law that grows in society. Settlement of civil disputes is not only done by state efforts lawÂ but custom society also often use the efforts in accordance with the customary law that applies in their place. The results of dispute resolution through traditional courts are decisions. In this study, analyzing the position of customary court decisions in civil court evidence if the decision has not been accepted by the disputing parties so that it requires legal remedies through a lawsuit or petition to the District Court.